Growth Improvement Corn Plant (Zea mays L.) F1 Local Variety of North Sumatera which has under Light Irradiation Gamma using NPK Mutiara Fertilizer - Aprilliansyah, M. Chelvin; Mustamu, Novilda Elizabeth; Saragih, Siti Hartati Yusida; Sitanggang, Kamsia Dorliana (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2025)
Corn (Zea mays L.) is a vital food ingredient that plays a significant role in food security in Indonesia, particularly in North Sumatra, and it has considerable potential for developing local corn varieties. This study aims to evaluate the effect of NPK Mutiara fertilizer on the growth of gamma-irradiated local corn (Zea mays L.) plants from North Sumatra. The research was conducted in Perbaungan Village, Bilah Hulu District, Labuhanbatu Regency, North Sumatra Province, from December to February. A completely randomized design (CRD) was employed, featuring one factor and five fertilizer dose treatments: control, 3 g/polybag, 6 g/polybag, 9 g/polybag, and 12 g/polybag, with four replications. The parameters observed included plant height, number of leaves, and stem diameter at 2, 4, 6, and 8 weeks after planting (WAP). The results showed that the application of NPK Mutiara fertilizer significantly affected plant height and the number of leaves at all ages of the plants. The treatment with the highest dose, 12 gr/polybag, produced the best results, with plant height reaching 160.70 cm at 8 WAP, leaves reaching 11.50 leaves, and stem diameter reaching 2.24 cm. NPK Mutiara fertilizer improved the growth of gamma-irradiated corn plants, with higher doses resulting in optimal growth. However, it is essential to apply the correct dosage to avoid harming the plants. This study recommends fertilization with the appropriate dose to optimize corn plant growth in North Sumatra.